2007
DOI: 10.1177/0003319706297741
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Liposomal Heparin Spraygel as an Add-on Treatment in the Management of Superficial Venous Thrombosis

Abstract: Superficial venous thrombosis usually resolves spontaneously in a few weeks. In most cases, treatment includes peroral analgesics or nonsteroidal anti-inflammatory drugs accompanied by the recommendation to wear elastic stockings and perform regular mild ambulation. In contrast to this "standard treatment," a recent ACCP guideline has recommended that patients affected by spontaneous superficial thrombophlebitis be treated with intermediate doses of unfractionated or low-molecular-weight heparin. This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…All patients underwent Doppler scanning of the deep venous system. Thrombus propagation was not encountered in any case during the three weeks observation period 95 …”
Section: Indications For Liposomes As Drug Carriers In Dermatologymentioning
confidence: 80%
See 2 more Smart Citations
“…All patients underwent Doppler scanning of the deep venous system. Thrombus propagation was not encountered in any case during the three weeks observation period 95 …”
Section: Indications For Liposomes As Drug Carriers In Dermatologymentioning
confidence: 80%
“…tretinoin) by hydration of the epidermis 37,38,118,119 Promising results have been obtained with liposomal encapsulated drugs in the treatment of acne, 36–40 xerosis, 51,52 atopic dermatitis, 53 psoriasis, 57,58 vitiligo, 66 superficial vein thrombosis 94,95 and hair removal 96–99 T4N5 containing liposomes protect the skin from UV‐induced carcinogenesis by promoting the DNA repair and by inhibiting immunosuppression 26,72–77 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, and 2005 two studies of the same design [11,12] concluded that LMWH is equally effective in comparison with topically applied heparin regarding the reduction of erythema, swelling and pain. Another study [13], compared LMWH with topically applied heparin in alleviating the above mentioned symptoms. In this study it was concluded that pain relief in the group which received topical heparin was better achieved than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Katzenschlager et al und Gorski et al verglichen 2003 und 2005 in randomisierten Studien die lokale Anwendung von Heparin-Spray-Gel vs. NMH 7 10 . Gorski et al fanden einen nichtsignifikanten Rückgang der OVT bei der Anwendung von NMH (RR: 0,30; 95 %-KI 0,03–2,70).…”
Section: Therapiemöglichkeiten Der Ovtunclassified